Comparison of the Chemical Properties of Forest Soil from the Silesian Beskid, Poland - Maria Zołotajkin; Adam Smoliński; Jerzy Ciba; Joanna Kluczka; Monika Skwira (Journal of Chemistry)
There is spruce forests degradation observed in the Silesian Beskid. The aim of the work was the assessment of parameters diversifying organic layers of soils in two forest areas: degraded and healthy spruce forests of Silesian Beskid. 23 soil samples were collected from two fields—14 soil samples from a degraded forest and 9 soil samples from a forest, where pandemic dying of spruce is not observed. Implementation of hierarchical clustering to experimental data analysis allowed drawing a conclusion that the two forest areas vary significantly in terms of content of aluminium extracted with solutions of barium chloride (Alexch), sodium diphosphate (Alpyr), and pHKCl and in the amount of humus in soil.